Assessment of hybrid vigor in yield traits of hybrid maize (Bangladesh Journal of Botany, 2025)
The analysis of the hybrid vigor of yield traits in high-yield maize variety Jikeyu 817 showed that it had a significant yield increasing effect, with increase of 2.50 and 17.60% compared to the control varieties, respectively. All yield traits exhibited a high level of heterosis, with relative heterosis ranging from 4.52 to 67.89%, with an average of 29.70%. The advantage of Chinese relatives ranges from 4.57 to 205.81%, with an average of 57.56%. The hybrid vigor index ranges from 104.47 to 301.71%, with an average of 157.80%. Among the traits, the hybrid vigor of yield is the highest, with relative hybrid vigor, mid-parent vigor, and hybrid vigor index of 67.89 , 205.81 and 301.71%, respectively.Bangladesh J. Bot. 54(3): 805-809, 2025 (September) Special